Enhanced Electro-Optical Properties of Electrically Controlled Birefringence Cells on Solution-Derived Lanthanum Oxide Films Treated with Ion Beam Irradiation. (2nd January 2015) - Lee, Jae-Won; Park, Hong-Gyu; Jeong, Hae-Chang; Seo, Dae-Shik
Abstract : Herein we demonstrate the improved performance of electrically controlled birefringence (ECB) cells fabricated on solution-derived La2 O3 films pre-treated with ion beam irradiation. Treatment by an ion-beam (IB) irradiation system and appropriate annealing temperature allowed La2 O3 surfaces to support homogeneous liquid crystal (LC) alignment. The EO characteristics of the aligned homogenous LCs and ECB modes in cells fabricated on La2 O3 layers were comparable to those of cells fabricated on polyimide, and IB-irradiated La2 O3 film surfaces showed good potential for use as an alignment layer.